LASIK for post penetrating keratoplasty astigmatism and myopia. Issue 9 (1st September 1999) - Webber, Suzanne K; Lawless, Michael A; Sutton, Gerard L; Rogers, Christopher M
Abstract : AIMS: To report the results of a series of patients who were treated with LASIK to correct post penetrating keratoplasty ametropia. METHODS: 26 eyes of 24 patients underwent LASIK to correct astigmatism and myopia after corneal transplantation; 14 eyes also received arcuate cuts in the stromal bed at the time of surgery. The mean preoperative spherical equivalent was −5.20D and the mean preoperative astigmatism was 8.67D. RESULTS: The results of 25 eyes are reported. The mean 1 month values for spherical equivalent and astigmatism were −0.24D and 2.48D respectively. 18 eyes have been followed up for 6 months or more. The final follow up results for these eyes are −1.91D and 2.92D for spherical equivalent and astigmatism. The patients undergoing arcuate cuts were less myopic but had greater astigmatism than those not. The patients receiving arcuate cuts had a greater target induced astigmatism, surgically induced astigmatism, and astigmatism correction index than those eyes that did not. One eye suffered a surgical complication. No eyes lost more than one line of BSCVA and all eyes gained between 0 and 6 lines UCVA. CONCLUSIONS: LASIK after penetrating keratoplasty is a relatively safe and effective procedure. It reduces both the spherical error and the cylindrical component of the ametropia. Correction of high astigmatism may be augmented by performing arcuate cuts in the stromal bed.